EDUCATIONAL LANDSCAPES IN THE CONTEXT OF THE DIGITAL EDUCATIONAL ENVIRONMENT - Boyarinov, Dmitry (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The concept of "educational map", as well as a number of related concepts such as "concept map", have been the subject of numerous studies in the field of pedagogy over the years. They are a tool for describing and analyzing the knowledge of a specific student at a specific point in time. Recently, there has been interest in the problem of generalization and aggregation of information contained in separate individual maps. The concept of "Concept Landscape" was proposed as an approach to solving this problem (Mühling, 2017). However, this concept is focused exclusively on the analysis of the knowledge structure of a group of students. Accordingly, the problem arises of finding a more general and more universal tool that allows us to organically fit aggregated educational maps into the structure of the digital educational environment. We propose to consider this environment as a context that unites all possible educational maps. In accordance with the proposed approach, by the educational landscape we mean the result of the aggregation of several educational maps, united by the digital educational environment as a common context. We also set ourselves the task of identifying technologies for the aggregation of educational maps. We consider superposition, inclusion and absorption as such technologies and disclose the content of these operations in our article. We also establish the main form of the formal description of the educational landscape - a graph with colored vertices and edges. We propose a five-component algorithm for constructing and processing an educational landscape and describe the content of all its stages in the article. In our study, we also give an answer to the question about the role of the educational landscape within the digital educational environment. This role is, in our opinion, multifactorial. The main factors include: the formation of a space of possible individual learning trajectories; analysis and forecasting of the group dynamics of knowledge and skills of students; creation of a tool for supporting the design of an digital educational environment.